Clinical and pathological factors associated with Ehrlichia canis in companion dogs - Espino-Solís, Gerardo Pavel; Flores-Lira, Erika Astrid; Barreras-Serrano, Alberto; García-Reynoso, Issa Carolina; de la Mora Covarrubias, Antonio; Jiménez Vega, Florinda; Escárcega-Ávila, Angélica (The Journal of Infection in Developing Countries, 2023)
Introduction: Canine monocytic ehrlichiosis (CME) is a disease caused by the Gram-negative bacteria Ehrlichia canis, a bacterium that affects domestic dogs but can also infect humans. The diagnosis implies a challenge due to its diversity in clinical manifestations. Methodology: The frequency of E. canis infection, risk factors, and clinical-pathological parameters associated with seropositivity were calculated with the PROC FREQ TABLES and PROC LOGISTIC procedures of the SAS statistical software. Results: The study showed a seroprevalence of 26.62% (156/586). Association between seropositivity and risk factors was found. The age and the presence of ticks including clinical signs such as anorexia, seizures, cough, petechiae, epistaxis, and hematochezia, as well as multiple blood and biochemical alterations were analyzed. The logistic regression analysis showed a high predictive power (c = 0.98) for CME for thrombocytopenia, leukopenia, and anemia. Conclusions: The high prevalence of E. canis in endemic areas makes its diagnosis difficult. Thus, clinical signs must be considered, along with blood and biochemical alterations, as a possible predictor of the disease.